A processing method for rough cutting hourglass worm on general NC lathe - Xinyang QIU; Yanqin ZHANG; Qiwu ZHOU; Fangyan ZHENG (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2019)
The manufacturing method of two spatial-orthogonal rotary axis linkage is usually used to cut hourglass worm. However, the traditional processing method of roughing tooth groove depends on the special machine, specific tool, and its processing efficiency is lower. To avoid these defects, a processing method of the rough cutting hourglass worm on general NC lathe without C-axis functions was presented in the paper. Based on the forming principle of the hourglass worm and the traditional processing steps, the machining principle of the new approach was elaborated. Key techniques such as the shape of the blade, the contours of tooth groove, tool path loop and the variable lead of worm, etc. were discussed. Macro-program of the new method was programmed based on Fanuc oi mate-tc CNC system, and tooth groove of the hourglass worm were trial manufactured on general NC lathe. Addendum axial pitch and a normal tooth thickness of the trial model were measured. It is noted that measurement results can satisfy the technological requirement. In conclusion, the new processing method of roughing hourglass worm is feasible and efficient.